Depresión post-Covid 19 y consumo de alcohol en adolescentes - Celi Gaona, Sofia Nickhol (2022)
Depression is an illness that makes difficult to perform at work, school, and the ability to deal with everyday life. On the other hand, alcohol consumption takes the second place in the adolescent population in America, for that reason is the importance of determining if post-COVID 19 depression influences alcohol consumption in adolescents. This study was a quantitative type, with a descriptive, exploratory, cross-sectional, and nonexperimental approach. The research was carried out in "Marieta de Veintimilla" high school in the city of Loja, with a sample of 72 adolescents, who had previously presented COVID 19. The results obtained indicated that there is no statistically significant relationship between the two variables. Minimal levels of depression were identified in the adolescent population and its relationship is not linked to alcohol consumption, despite this, it is recommended to include mental health promotion programs